RANCANG BANGUN APLIKASI E-COMMERCE PENJUALAN JAMU HERBAL BERBASIS WEBSITE PADA USAHA JAMU HERBAL DENGAN MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) - Donni Donni Halomoan; Devi Yunita (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Herbal Medicine Shop is a business engaged in the concoction of healthy herbal herbal drinks. which processes a beverage product in the form of a concoction to become a ready-to-drink drink. All activities in the herbal herbal shop business from stock of goods, marketing to sales transactions are still carried out manually, namely by recording in books/papers. To overcome these problems, the author designs e-commerce application for selling S Herbal Herbs based on a website in the Herbal Medicine Business Using the Rapid Application Development (RAD) Method. Then the data collection method used by the author is interviews and observation. The approach method used is an object-oriented system approach with system design tools using the Unified Modeling Language (UML). There are several tools used to build this application, namely Hypertext Preprocessor (PHP), MySQL for the database then Sublime Text is used to write the program code. The expected goal in building this e-commerce application is to help manage stock data, customer data, order data and sales transactions at the Sidomuncul herbal herbal shop business. With this e-commerce application, it can facilitate transactions with high speed compared to previous transactions, and can shorten the time and place in conducting transactions.